SEASONAL TRENDS IN ANTIBIOTIC USAGE AMONG PAEDIATRIC OUTPATIENTS - Edita Alili-Idrizi; Merita Dauti; Ledjan Malaj (European Scientific Journal, ESJ, 2014)
The aim of this study was to analyze two aspects, the first one being the seasonal variations in antibiotic usage in different age groups and the seasonal prescription patterns of commonly used antibiotics in paediatric outpatients, the other one being the correlation of antibiotics with age and clinical diagnosis. Surveillance of antibiotic use was done during 01 January – 31 December, 2012 in the outpatient department of a paediatric hospital in Tetovo. Drug data and patient characteristics were computed using Ms. Excel 2007 and the SPSS (version 19.0) packages. Among the total number of 7956 patients analyzed during the period of one year, 3151 (39.6 %) of them were prescribed antibiotics. From the different age group, the study showed that special attention should be paid to toddlers (> 1 - ≤ 3 years)-those utilizing significant percentage of the antibiotic year’s supply. Seasonal variation in antibiotic usage was strictly linked with the age of patients. Significant fluctuations of monthly use of antibiotics were observed for cephalosporins, combinations of antibiotics and macrolides. There was no significant seasonal fluctuation for penicillins. Respiratory tract infections were identified as a factor considerably elevating monthly drugs usage frequency. Usage of antibiotics was significantly correlated with group age. There was a correlation between the percentage of children given antibiotics for respiratory tract infections and the overall paediatric antibiotic prescribing rate. Results from our study have shown that a continuous surveillance of antibiotic use and resistance in the community are necessary to develop and implement guidelines for antibiotic use.